High Durability Sliding TENG with Enhanced Output Achieved by Capturing Multiple Region Charges for Harvesting Wind Energy - He, Wencong; Liu, Yunchuan; Jin, Junhao; Cai, Jiahao; Wan, Buyong; Chen, Jie; Yang, Xiaohong; Hu, Chenguo (Nano-Micro Letters, 2026)
Improving the electric output and durability of triboelectric nanogenerator (TENG) remains a great challenge. In sliding-mode TENG, surface charge dissipation and charge leakage caused by the volume effect result in serious energy waste. In this work, a durable dual output mode TENG (DDO-TENG), which includes alteranting current and direct current output modes, is designed to capture the dissipating charges in the surface of charge space accumulation area and the inner leakage charge in porous network to further improve the output performance of sliding TENGs. The output charge density of DDO-TENG reaches 0.847 mC m−2, which is 2.39 times as that of the single mode device. In addition, it has strong durability, remaining 95.7% after over 271 k cycles, and it can continuously power electronics by harvesting wind energy. This work provides a strategy for achieving the improvement on output performance and durability and expands the application of TENG. Highlights: 1 A dual output mode triboelectric nanogenerator for capturing multiple regions charges is proposed. 2 Achieving a 139% improvement in charge transferring rate compared to traditional device. 3 A charge density of 846.7 μC m−2 is achieved based on microscale dielectric material. 4 The device can supply power for remote road signs under wind energy.